2006
DOI: 10.1080/09548980601064846
|View full text |Cite
|
Sign up to set email alerts
|

Entorhinal cortex grid cells can map to hippocampal place cells by competitive learning

Abstract: 'Grid cells' in the dorsocaudal medial entorhinal cortex (dMEC) are activated when a rat is located at any of the vertices of a grid of equilateral triangles covering the environment. dMEC grid cells have different frequencies and phase offsets. However, cells in the dentate gyrus (DG) and hippocampal area CA3 of the rodent typically display place fields, where individual cells are active over only a single portion of the space. In a model of the hippocampus, we have shown that the connectivity from the entorh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
204
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(212 citation statements)
references
References 43 publications
7
204
1
Order By: Relevance
“…Models have shown that individual fields can be generated by a combination of only 10-50 grid cells with variable grid spacing and grid orientation but overlapping spatial phase (Solstad et al, 2006). In a second type of mechanism, place cells receive inputs from grid cells with variable spacing, orientation, and spatial phase (Rolls et al, 2006). Single-peaked place fields are generated from the resulting distribution of activity peaks by competitive Hebbian learning processes.…”
Section: From Grid Cells To Place Cells or Vice Versamentioning
confidence: 99%
“…Models have shown that individual fields can be generated by a combination of only 10-50 grid cells with variable grid spacing and grid orientation but overlapping spatial phase (Solstad et al, 2006). In a second type of mechanism, place cells receive inputs from grid cells with variable spacing, orientation, and spatial phase (Rolls et al, 2006). Single-peaked place fields are generated from the resulting distribution of activity peaks by competitive Hebbian learning processes.…”
Section: From Grid Cells To Place Cells or Vice Versamentioning
confidence: 99%
“…First, weak spatial inputs may be sufficient for place-cell formation. Sharply confined firing fields may be generated by local mechanisms in the hippocampal network, such as recurrent inhibition (de Almeida et al 2009;Monaco and Abbott 2011), Hebbian plasticity (Rolls et al 2006;Savelli and Knierim 2010), or active dendritic properties (Smith et al 2013). Alternatively, place cells may be generated from other classes of spatially modulated cells, such as border cells, which have adult-like properties from the very first day of exploration outside the nest (Bjerknes et al 2014).…”
Section: Upstream Of Place Cells: Grid Cells and Other Cell Typesmentioning
confidence: 99%
“…This indicates that with the population code expressed by grid cells it is possible to keep a unique orientation correspondence across environments in spite of the orientation symmetry of the grids, and to differentiate locations in an environment by the relative spatial phases of the grid fields. To represent places on a larger scale, multiple grid spacings are needed [37][38][39][40] .…”
Section: Grid Realignment In Multiple Environmentsmentioning
confidence: 99%